Variación del área agrícola en el distrito La Yarada Los Palos, Tacna, Perú - Alvarado Huapaya, Ana Isabel (2020)
Population growth and the increasing use of groundwater has favored the extension of the agricultural area in the last twenty-one years in the district of La Yarada Los Palos. In this study, we seek to analyze the changes in agricultural extension and identify trends through remote sensing and multitemporal spatial analysis. Landsat 5TM and Landsat 8 OLI satellite images were used for the period 2000-2020 to identify agricultural uses in the study area. The results show that the agricultural area increased by 265.84%, a figure that would double in the next ten years, according to the polynomial regression. These findings provide a basis for decision-making and management of future water, agricultural and social projects.